Hyperosmolar Therapy in Pediatric Severe Traumatic Brain Injury-A Systematic Review - Stopa, Brittany M.; Dolmans, Rianne G.F.; Broekman, Marike L.D.; Gormley, William B.; Mannix, Rebekah; Izzy, Saef (Lippincott Williams & Wilkins, 2019)
OBJECTIVES: Traumatic brain injury is a leading cause of hospital visits for children. Hyperosmolar therapy is often used to treat severe traumatic brain injury. Hypertonic saline is used predominantly, yet there remains disagreement about whether hypertonic saline or mannitol is more effective. DATA SOURCES: Literature search was conducted using Pubmed, Cochrane, and Embase. Systematic review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. STUDY SELECTION: Retrospective and prospective studies assessing use of hyperosmolar therapy in pediatric patients with severe traumatic brain injury were included. DATA EXTRACTION: Two independent authors performed article review. Two-thousand two-hundred thirty unique articles were initially evaluated, 11 were included in the final analysis, with a total of 358 patients. Study quality was assessed using Modified Newcastle-Ottawa Scale and Jadad score. DATA SYNTHESIS: Of the 11 studies, all evaluated hypertonic saline and four evaluated both hypertonic saline and mannitol. Nine reported that hypertonic saline lowered intracranial pressure and two reported that mannitol lowered intracranial pressure. The studies varied significantly in dose, concentration, and administrations schedule for both hypertonic saline and mannitol. Five studies were prospective, but only one directly compared mannitol to hypertonic saline. The prospective comparison study found no difference in physiologic outcomes. Clinical outcomes were reported using different measures across studies. For hypertonic saline-treated patients, mechanical ventilation was required for 6.9-9 days, decompressive craniectomy was required for 6.25-29.3% of patients, ICU length of stay was 8.0-10.6 days, in-hospital mortality was 10-48%, and 6-month mortality was 7-17%. In mannitol-treated patients, ICU length of stay was 9.5 days, in-hospital mortality was 56%, and 6-month mortality was 19%. CONCLUSIONS: Both hypertonic saline and mannitol appear to lower intracranial pressure and improve clinical outcomes in pediatric severe traumatic brain injury, but the evidence is extremely fractured both in the method of treatment and in the evaluation of outcomes. Given the paucity of high-quality data, it is difficult to definitively conclude which agent is better or what treatment protocol to follow.
Keywords: closed head injuries; hypertonic saline solution; mannitol; pediatric intensive care units; pediatrics; traumatic brain injury; Taverne; Critical Care and Intensive Care Medicine